Tas'ir (Price Control) in Islamic Law (American Journal of Islam and Society, 1994)
The market (suq or Bazar)has a distinctive place in the history ofIslamic civilization. Makkah and MadInah were major trade centers at thetime of the advent of Islam, and the prophet was himself an active marketparticipant and reformer. There were famous markets-'Ukkaz, Majannah,and Dhu al Majaz- in pre-Islamic Arabia that commonly held fairsduring the pilgrimage season. This practice was conhued after the appearanceof Islam, for when the new Muslims felt that it might be sinfulfor them to trade in such places (al Zubayli 1984), the following versewas revealed: "There is no sin if you seek the bounty of your Lotd(during the pilgrimage)" (Qur'an 2:198).The main theme here is religious: allaying the fear of indulging insin. However, it is Significant that this potentially sinful activity was refe d to in such dignified term as "seeking the bounty of your Lotd."Elsewhere in the Qur'an, we find passages dealing withthe market's culturalElspects, such as the verse that asks whether it is proper for the Prophetto mingle with the common people in the market place. The answerreceived was that prophets, just like everybody else, ate free to interactand engage in commercial tnmsactions in the mark& "And they say:What sort of a messenger is this, who eats food and walk- through thestreets? Why has not an angel been sent down to him to be a Warner withhim?" (Qur'an 257) and "And the Messengers whom We sent before youwere all (men) who ate food and walked through the streets" (Quran25:20). The second citation refers to market activity in a mainly econofnicand historical context, one that highlights the market's role in providingfoodstuffs and the fact that all prophets mixed with their people on thebasis of equality. In other words, they were ordinary men whose spiritualvalue was not compromised by engaging in market activities.These verses characterize Islam’s worldview in gened and its viewof the market’s diverse nature in particular. Islam reaffirms its holistic approachto life and informs us that the market is an arena for the combinedinterplay of culture, religion, economics, and history. This was partly due,perhaps, to the Prophet’s own commercial experience and acumen, whichhe put to good use as his future wife’s (Khadijah) trusted agent and thatled eventually to the reform of Arabian commercial practices. These reformssought to purify the market of practices that differed from Islamicideals of fair play, honesty, and justice. In many ways, a market is likean open theater, for it displays the unfolding of a portion of a civilization’sbest achievements as well as its worst weaknesses and pitfalls.One frequent issue is the need to recognize the free market principle:the goveming of trade solely by the natural interplay of the economicforces of supply and demand. Only in such a market, it is argued, is oneurged to strive and compete with his/her peers in pursuit of betterproducts or services. No market can exist without a profit motive, and theright to make a profit must never be eliminated. Thus a market regulatormust be concerned with asceltaining that legitimate profit does not exceedthe limits of fair gain and that an individual’s greed and desire for profitare controlled. The intention is to ensure that skilled market operators donot take advantage of an unsuspecting customer’s ignorance and naivety.Broadly speaking, one may say that this was the main goal of thenew Islamic rules introduced into the Arabian market’s economic life. Nolaw dealing with the quantitative limits of profit was promulgated, forprofit is the result of supply and demand and so is not a concern of thelaw. The law’s role is limited to ensuring the market’s morality, as wellas the propriety and fairness of its participants and their activities (i.e.,prohibiting fraud and misrepresentation), and implementing precautionarymeasures to prevent or rectify unfair trading practices ...